Pressure jump interface law for the Stokes–Darcy coupling: confirmation by direct numerical simulations - Carraro, T.; Goll, C.; Marciniak-Czochra, A.; Mikelić, A. (Journal of fluid mechanics, 2013)
It is generally accepted that the effective velocity of a viscous flow over a porous bed satisfies the Beavers–Joseph slip law. To the contrary, the interface law for the effective stress has been a subject of controversy. Recently, a pressure jump interface law has been rigourously derived by Marciniak-Czochra and Mikelić. In this paper, we provide a confirmation of the analytical result using direct numerical simulation of the flow at the microscopic level. To the best of the authors’ knowledge, this is the first numerical confirmation of the pressure interface law in the literature.